Coordinate Stability Analysis of PT PLN Customers with Variance and DBSCAN Clustering: Pontianak Case Study: Analisis Stabilitas Koordinat Pelanggan PT PLN dengan Variansi dan DBSCAN Clustering: Studi Kasus Pontianak - Oktavia Arnelliza Ayu; Agus Haryadi; Nilamsari Kusumastuti; Muhammad Faqih Dzulqarnain (JRST (Jurnal Riset Sains dan Teknologi), 2026)
PT PLN (Persero) is a major electricity provider in Indonesia that relies on accurate spatial data management to support various operations, such as electricity bill delivery and network expansion planning. Accurate spatial data also plays an important role in making strategic decisions regarding future network development. This research aims to identify stable coordinate points and analyze clustering results using DBSCAN (Density-Based Spatial Clustering of Applications with Noise) on postpaid customer spatial data in Pontianak City, with a focus on the geographic coordinate point distance of customer homes. The dataset used includes information on the home coordinates of postpaid customers of PT PLN (Persero) Pontianak City from February to July 2024. Variance analysis was applied to determine which coordinate points were considered stable, while DBSCAN was used to determine clusters and identify noise based on data density. With an epsilon parameter of 0.0036 and minimum points (minPts) of 15, the results show two main clusters, the first cluster consists of 50 points and the second cluster consists of 18 coordinate points of customer house locations. In addition, no noise was detected in the data set. The results of this research provide strategic benefits for PT PLN. The main cluster allows PLN to prioritize network development in areas with high customer density to maintain optimal service quality. Meanwhile, although no noise was detected in this study, if there are low-density areas in other analyses, special strategies need to be designed to support service improvement in these areas.   ABSTRAK (Bahasa Indonesia) PT PLN (Persero) merupakan perusahaan penyedia listrik utama di Indonesia yang mengandalkan pengelolaan data spasial yang akurat untuk mendukung berbagai operasi, seperti pengiriman tagihan listrik dan perencanaan perluasan jaringan. Data spasial yang akurat juga memainkan peran penting dalam pengambilan keputusan strategis terkait pengembangan jaringan di masa depan. Penelitian ini bertujuan untuk mengidentifikasi titik koordinat yang stabil serta menganalisis hasil klasterisasi menggunakan DBSCAN (Density-Based Spatial Clustering of Applications with Noise) pada data spasial pelanggan pasca bayar di Kota Pontianak, dengan fokus pada jarak titik koordinat geografis rumah pelanggan. Dataset yang digunakan mencakup informasi titik koordinat rumah pelanggan pasca bayar PT PLN (Persero) Kota Pontianak dari Februari hingga Juli 2024. Analisis variansi diterapkan untuk menentukan titik koordinat yang dianggap stabil, sementara DBSCAN digunakan untuk menentukan klaster dan mengidentifikasi noise berdasarkan kepadatan data. Dengan parameter epsilon  sebesar 0,0036 dan minimum points (minPts) sebanyak 15, hasil menunjukkan dua cluster utama yaitu cluster pertama terdiri dari 50 titik dan cluster kedua terdiri dari 18 titik koordinat lokasi rumah pelanggan. Selain itu, tidak ada noise yang terdeteksi dalam data set. Hasil penelitian ini memberikan manfaat strategis bagi PT PLN. Klaster utama memungkinkan PLN dapat memprioritaskan pengembangan jaringan diarea dengan kepadatan pelanggan tinggi guna menjaga kualitas layanan tetap optimal. Sementara itu, meskipun tidak terdeteksi noise pada penelitian ini, jika terdapat area dengan kepadatan rendah pada analisis lain, strategi khusus perlu dirancang untuk mendukung peningkatan layanan diarea tersebut